Pengaruh Persepsi Manfaat, Hedonic Motivation terhadap Penerimaan dalam Niat Gabung Membership Gym di Semarang - Harmanda Berima Putra; Wisna Rizki Ramadan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to examine the effect of perceived benefits and hedonic motivation on the intention to join gym membership in Semarang. The research method used is a quantitative method. The data collection method used is an online quetioner survey with a questionnaire. The research sample is gym consumers in Semarang with a sample size of 151 people. The results of the SEM analysis using SMART PLS software show perceived benefits and hedonic motivation is proven to have a positive effect on the intention.